Perovskite light emitting diode and preparation method thereof
By introducing PEI organic solution spin coating method into perovskite light emitting diodes, the problems of luminescent layer quenching and carrier imbalance are solved, the luminescence efficiency and performance of the device are improved, and the high total solvent processing is achieved Performance preparation.
Patent Information
- Application Number
- CN202411343703.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-14
AI Technical Summary
During the preparation process, existing perovskite light emitting diodes have problems such as rapid quenching of the light emitting layer and carrier imbalance, which leads to non-radiation loss and makes it difficult to achieve high-performance full solvent processing.
The interface layer was prepared by spin coating of PEI organic solution, located between the perovskite luminescent layer and the electron transport layer, and the electrical properties of the device were controlled by controlling the concentration of the PEI organic solution, combined with the solution method and the evaporation method, perovskite was prepared. Light emitting diode.
Effectively suppress interface losses, improve energy relationships, improve luminous efficiency, simplify manufacturing processes, and enhance electric-optical conversion efficiency.
Smart Images

Figure CN119317303A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of optoelectronic materials and relates to a perovskite light emitting diode and a preparation method thereof. Background Art
[0002] Perovskite light-emitting diodes (PeLEDs) prepared based on new organic-inorganic composite perovskite materials have the advantages of simple preparation process, rich raw material sources, and wide color gamut, and are considered to be one of the strong competitors for the next generation of display technology. However, most perovskite light-emitting diodes (PeLEDs) use thermal deposition methods to prepare electron transport layers on top of the perovskite layer. In order to achieve low-cost PeLEDs and their scalable preparation, the all-solution device process is the most urgent problem to be solved. The use of polar solvents to process the upper layer of perovskites will lead to rapid quenching of the light-emitting layer, while the use of non-polar solvents will cause the perovskite light-emitting film to dissolve again, which makes it difficult to achieve high-performance PeLED devices processed by all solvents.
[0003] In addition, research on improving effective carrier injection and transport, efficient light-emitting layer structure design, and optimizing interface energy levels has scientific guiding value for improving the performance of PeLED devices. Since the perovskite light-emitting layer is very critical in the device's electro-optical conversion, especially by suppressing the crystal defects of the light-emitting layer and improving the balanced transport of carriers in the semiconductor functional layer to achieve effective composite luminescence, it is of great significance for the development of low-cost PeLED. Summary of the invention
[0004] The present invention aims to solve the problems and defects in the above-mentioned prior art. The present invention provides a perovskite light-emitting diode and a preparation method thereof, which is used to solve the luminescence quenching caused by internal defects of the perovskite light-emitting diode in the prior art and the non-radiative loss caused by carrier imbalance, and improve the energy relationship of each functional layer, thereby improving the luminescence efficiency of the device.
[0005] On the one hand, the present invention provides a perovskite light-emitting diode, which includes a hole transport layer, a perovskite light-emitting layer, an electron transport layer, an electron injection layer and a cathode arranged in sequence on an anode substrate, and also includes an interface layer made by a PEI organic solution spin coating method, wherein the interface layer is arranged between the perovskite light-emitting layer and the electron transport layer.
[0006] Furthermore, the present invention regulates the electrical properties of the perovskite light-emitting diode by controlling the concentration of the PEI organic solution in the interface layer. When the concentration of the PEI organic solution is 0.05 to 1 mg / mL, as the concentration of the PEI organic solution in the interface layer increases, the current density decreases. When the PEI organic concentration is relatively low, the interface layer plays a good role in suppressing interface loss and improving energy relations, promoting the effective recombination of carriers, and significantly improving the brightness of the light-emitting diode.
[0007] On the other hand, the present invention provides a method for preparing a perovskite light-emitting diode, comprising: using a solution method to sequentially spin-coat a hole transport layer, a perovskite light-emitting layer, the interface layer, and an electron transport layer on an anode substrate;
[0008] Then, an electron injection layer and a cathode are sequentially vacuum-deposited on the electron transport layer.
[0009] Furthermore, the method for preparing a perovskite light-emitting diode provided by the present invention comprises the following steps:
[0010] S1. Surface treatment of the anode substrate after cleaning and drying;
[0011] S2. Spin-coating PEDOT:PSS on the surface of the anode substrate described in S1 and annealing to obtain a hole transport layer;
[0012] S3. Spin-coating a perovskite precursor solution on the hole transport layer described in S2, and obtaining a perovskite light-emitting layer after heat treatment;
[0013] S4. After spin coating the PEI organic solution on the perovskite light-emitting layer described in S3, vacuum drying is performed to obtain an interface layer;
[0014] S5. Spin coating the TPBi solution on the interface layer described in S4 to obtain an electron transport layer;
[0015] S6. Vacuum evaporate an electron injection layer and a cathode on the electron transport layer described in S5.
[0016] Furthermore, the method for preparing the perovskite light-emitting diode provided by the present invention specifically comprises the following steps:
[0017] S1. The anode substrate is an ITO substrate or a FTO substrate. The anode substrate is placed in deionized water, anhydrous ethanol, acetone and isopropanol for ultrasonic cleaning in turn. The ultrasonic cleaning time for each time is 20 to 30 minutes. After the ultrasonic cleaning, the anode substrate is dried. Then, the dried anode substrate is surface treated, i.e., plasma bombardment surface treatment or ultraviolet light treatment, to achieve further cleaning.
[0018] S2. PEDOT:PSS solution and water were ultrasonically mixed at a volume ratio of 1:1 for 2 hours. The mixed PEDOT:PSS was filtered through a 0.22 μm aqueous filter head and then dripped onto the anode substrate. Then, a hole transport layer film was formed by spin coating at a rotation speed of 2000-4000 rpm / min and a spin coating time of 50-60 seconds. After the spin coating, the film was annealed at 130-150°C for 15-20 minutes in an air environment to obtain a hole transport layer.
[0019] S3. Dissolve CsBr, PbBr2 and P123 in N,N-dimethylformamide (DMF) or dimethyl sulfoxide (DMSO) at a mass ratio of 8.33:8.3:0.3 to prepare a perovskite precursor solution. In a nitrogen environment of a glove box, spin coat the perovskite precursor solution at a speed of 2000-4000 rpm / min for 50-60 s. After spin coating, continue to perform heat treatment in a nitrogen environment at a temperature of 50-80°C for 1-3 min to obtain a light-emitting layer.
[0020] S4. Dissolve PEI in isopropanol to prepare a PEI organic solution with a concentration of 0.05-1 mg / mL. Continue to spin-coat the PEI organic solution in the nitrogen environment of the glove box. The spin-coating speed of the PEI organic solution is 2000-5000 rpm / min, and the spin-coating time is 50-65 s. After the spin coating is completed, transfer to a small transition chamber in the glove box, perform a vacuum treatment for 10 minutes, and stand in a vacuum environment for 0.5-1 hour to obtain an interface layer.
[0021] S5. Dissolve TPBi in DMF or DMSO to prepare a TPBi solution, wherein the concentration of the TPBi solution is 3 to 5 mg / mL. Transfer the perovskite light-emitting diode after preparing the interface layer in step S4 to a glove box, and spin-coat the TPBi solution. The spin-coating speed of the TPBi solution is 1000 to 3000 rpm / min, and the spin-coating time is 50 to 65 s to obtain an electron transport layer.
[0022] S6. After all functional layers are spin-coated, the perovskite light-emitting diode with the electron transport layer obtained in S5 is transferred into a vacuum evaporation chamber for evaporation of the electron injection layer and the cathode. The evaporated electron injection layer is LiF, and the thickness of the electron injection layer is 0.3 to 1 nm. The vacuum evaporated cathode is metallic silver or aluminum, and the thickness of the cathode is 80 to 150 nm.
[0023] Compared with the prior art, the technical solution provided by the present invention has at least the following beneficial effects or advantages:
[0024] The preparation method of the perovskite light-emitting diode provided by the present invention is different from the process of combining the traditional solution method and the evaporation method. The present invention adopts the solution method in the preparation of the functional layer. Specifically, all key functional layers of the perovskite light-emitting diode, including the hole transport layer, the perovskite light-emitting layer, the interface layer and the electron transport layer, are successfully prepared by the solution method and the spin coating technology. Compared with the traditional technology of the electron transport layer partially using the evaporation method, the present invention completely abandons the evaporation step and adopts the solution method to prepare each functional layer. Among them, the PEI interface layer introduced in the present invention overcomes the damage caused to the perovskite light-emitting layer by the solution method during the preparation of the electron transport layer, effectively protects the perovskite light-emitting layer, and significantly improves the performance of the perovskite light-emitting diode. The present invention not only simplifies the manufacturing process, but also improves the energy level relationship between the perovskite light-emitting layer and the electron transport layer, suppresses interface loss, and enhances the electro-optical conversion efficiency through the ingenious combination of the full solution method and the PEI interface layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 Schematic diagram of the structure of a perovskite light-emitting diode.
[0026] Figure 2 Schematic diagram of the structure of PEI molecule.
[0027] Figure 3 This is the JV curve of the perovskite light-emitting diode.
[0028] Figure 4 This is the LV curve of the perovskite light-emitting diode. DETAILED DESCRIPTION
[0029] The technical scheme of the present invention is described below in conjunction with the embodiments, but the present invention is not limited to the following embodiments. The experimental methods and detection methods described in each embodiment are conventional methods unless otherwise specified; the reagents and materials described are all commercially available unless otherwise specified.
[0030] Example 1
[0031] This embodiment provides a method for preparing a perovskite light emitting diode.
[0032] The present invention provides a perovskite light-emitting diode, such as Figure 1 As shown, the structure of the perovskite light-emitting diode includes: a hole transport layer, a perovskite light-emitting layer, an interface layer, an electron transport layer, an electron injection layer and a cathode arranged in sequence on one side of the anode substrate; the interface layer is made by PEI organic solution spin coating method.
[0033] The method for preparing the perovskite light-emitting diode of the present invention comprises the following steps:
[0034] (1) Cleaning and drying the anode substrate;
[0035] (2) spin coating PEDOT:PSS on the surface of the anode substrate described in step (1) and annealing to obtain a hole transport layer;
[0036] (3) spin coating a perovskite precursor solution on the hole transport layer described in step (2), and obtaining a perovskite light-emitting layer after heat treatment;
[0037] (4) spin coating the PEI organic solution on the perovskite light-emitting layer described in step (3), and vacuum drying to obtain an interface layer;
[0038] (5) spin coating the TPBi solution on the interface layer described in step (4) to prepare an electron transport layer;
[0039] (6) Vacuum evaporating an electron injection layer and a cathode on the electron transport layer described in step (5).
[0040] Wherein, the anode substrate in the step (1) is an ITO substrate or a FTO substrate, and the anode substrate is placed in deionized water, anhydrous ethanol, acetone and isopropanol for ultrasonic cleaning in sequence, and the ultrasonic time for each time is 20 to 30 minutes. After the ultrasonic treatment, the anode substrate is dried, and then the dried anode substrate is surface treated, i.e., plasma bombardment surface treatment or ultraviolet light treatment, to achieve further cleaning.
[0041] The PEDOT:PSS (poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonate)) in step (2) is a PEDOT:PSS solution and water in a volume ratio of 1:1, and the mixing time is 2 hours. The mixed PEDOT:PSS solution is filtered through a 0.22 μm aqueous filter head and then dripped onto the anode substrate, and then a hole transport layer film is formed by spin coating, with a rotation speed of 2000 to 4000 rpm / min and a spin coating time of 50 to 60 seconds. After the spin coating is completed, annealing is performed at 130 to 150° C. in an air environment for 15 to 20 minutes.
[0042] The perovskite precursor solution in step (3) is prepared by dissolving CsBr, PbBr2 and P123 (polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer) in N,N-dimethylformamide (DMF) or dimethyl sulfoxide (DMSO) in a mass ratio of 8.33:8.3:0.3. In a nitrogen environment of a glove box, the perovskite precursor solution is spin-coated at a speed of 2000-4000 rpm / min and a spin-coating time of 50-60 s. After the spin coating is completed, heat treatment is continued in a nitrogen environment at a temperature of 50-80°C and a heat treatment time of 1-3 min.
[0043] The PEI (polyethyleneimine) organic solution in step (4) is PEI dissolved in isopropanol at a concentration of 0.05 to 1 mg / mL, wherein the molecular structure of PEI is as follows: Figure 2 The spin coating speed of the PEI organic solution is 2000-5000 rpm / min, and the spin coating time is 50-65 s. After the spin coating is completed, it is left to stand in a vacuum environment for 0.5-1 h.
[0044] The TPBi (1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene) solution in step (5) is TPBi dissolved in DMF or DMSO, and the concentration of the TPBi solution is 3 to 5 mg / mL. The spin coating speed of the TPBi solution is 1000 to 3000 rpm / min, and the spin coating time is 50 to 65 s.
[0045] The vacuum-evaporated electron injection layer in step (6) is LiF, and the thickness of the electron injection layer is 0.3-1 nm. The vacuum-evaporated cathode is metallic silver or aluminum, and the thickness of the cathode is 80-150 nm.
[0046] Example 2
[0047] This embodiment provides a method for preparing a perovskite light emitting diode.
[0048] The structure of the perovskite light-emitting diode device provided in this embodiment is as follows Figure 1 As shown, anode (ITO) / hole transport layer (PEDOT:PSS:deionized water) / perovskite light-emitting layer / interface layer (isopropyl alcohol) / electron transport layer (TPBi) / / electron injection layer (LiF) / cathode (Ag).
[0049] 1. Cleaning of anode ITO substrate
[0050] The ITO substrate was ultrasonically cleaned in deionized water, anhydrous ethanol, acetone and isopropanol in turn, and the ultrasonic time was 20 minutes each time. After the ultrasonic treatment, the ITO substrate was dried in an oven for more than 2 hours to ensure that the ITO substrate was completely dry and ready for use. The cleaned and dried ITO substrate was treated with ultraviolet light for 5 minutes to facilitate the uniform distribution of the hole transport layer solution on the ITO substrate.
[0051] 2. Preparation of hole transport layer
[0052] (1) Preparation of hole transport layer solution: Take out the PEDOT:PSS solution from a 4°C refrigerator, leave it for half an hour until the solution returns to room temperature, mix deionized water and the PEDOT:PSS aqueous solution in a volume ratio of 1:1 to obtain a hole transport layer solution.
[0053] (2) Preparation of hole transport layer: The hole transport layer solution was filtered through a 0.22 μm aqueous filter head and then dropped onto the ITO substrate. The solution was spin-coated at a speed of 3000 rpm / min for 60 s and then annealed in air at 130° C. for 20 min. The thickness of the hole transport layer was 10 nm.
[0054] 3. Preparation of perovskite light-emitting layer
[0055] (1) Preparation of perovskite precursor solution: CsBr, PbBr2 and P123 reagents were mixed in a mass ratio of 83.3:8.3:0.3 and dissolved in DMSO to obtain a perovskite precursor solution.
[0056] (2) Preparation of perovskite light-emitting layer: Figure 1 The stacking order of the device structure shown is that the ITO substrate coated with the hole transport layer is transferred into the glove box and spin-coated with the perovskite precursor solution. The spin coating amount is 75 μL, the spin coating speed is 2000 rpm / min, and the spin coating time is 60 s. Then, heat treatment is performed at a temperature of 60°C for 1.5 min. The thickness of the perovskite light-emitting layer is 20 nm.
[0057] 4. Preparation of the Interface Layer
[0058] (1) Preparation of interface layer solution: The interface layer solution is untreated isopropanol liquid.
[0059] (2) Preparation of interface layer: After preparing the perovskite light-emitting layer, the interface layer was treated in the glove box. The spin coating amount was 75 μL of isopropanol liquid, the spin coating speed was 4000 rpm / min, and the spin coating time was 60 s. Then, the existing device (i.e., anode / hole transport layer / perovskite light-emitting layer / interface layer) was placed in a small transition chamber of the glove box, vacuumed for 10 minutes, and allowed to stand for 1 hour for vacuum drying.
[0060] 5. Preparation of Electron Transport Layer
[0061] (1) Preparation of electron transport layer solution: The electron transport material TPBi was dissolved in DMSO to prepare a TPBi solution with a concentration of 5 mg / mL.
[0062] (2) Preparation of electron transport layer: After the interface layer is prepared, the device is transferred from the small transition chamber to the glove box to prepare the electron transport layer. The spin coating amount is 75 μL, the spin coating speed is 2000 rpm / min, and the spin coating time is 60 s.
[0063] 6. Preparation of electron injection layer and cathode
[0064] After the electron transport layer is prepared, the device is transferred into a vacuum evaporation chamber for evaporation of the electron injection layer (LiF) and the cathode (Ag), wherein the thickness of the evaporated electron injection layer is 1 nm, and the thickness of the evaporated cathode is 100 nm.
[0065] 7. Electrical performance characterization
[0066] After the silver electrode cathode evaporation is completed, the device is placed in a glove box for characterization of electrical properties, namely the device's current, voltage, brightness, efficiency and other electrical properties.
[0067] Example 3
[0068] This embodiment provides a method for preparing a perovskite light emitting diode.
[0069] The structure of the perovskite light-emitting diode device provided in this embodiment is as follows Figure 1 As shown, anode (ITO) / hole transport layer (PEDOT:PSS:deionized water) / perovskite light-emitting layer / interface layer (PEI) / electron transport layer (TPBi) / / electron injection layer (LiF) / cathode (Ag).
[0070] 1. Cleaning of anode ITO substrate
[0071] The ITO substrate was ultrasonically cleaned in deionized water, anhydrous ethanol, acetone and isopropanol in turn, and the ultrasonic time was 20 minutes each time. After the ultrasonic treatment, the ITO substrate was dried in an oven for more than 2 hours to ensure that the ITO substrate was completely dry and ready for use. The cleaned and dried ITO substrate was treated with ultraviolet light for 5 minutes to facilitate the uniform distribution of the hole transport layer solution on the ITO substrate.
[0072] 2. Preparation of hole transport layer
[0073] (1) Preparation of hole transport layer solution: Take out the PEDOT:PSS aqueous solution from a 4°C refrigerator, leave it for half an hour until the solution returns to room temperature, mix deionized water and the PEDOT:PSS aqueous solution in a volume ratio of 1:1 to obtain a hole transport layer solution.
[0074] (2) Preparation of hole transport layer: The hole transport layer solution was filtered through a 0.22 μm aqueous filter head and then dropped onto the ITO substrate. The solution was spin-coated at a speed of 3000 rpm / min for 60 s and then annealed in air at 130° C. for 20 min. The thickness of the hole transport layer was 10 nm.
[0075] 3. Preparation of perovskite light-emitting layer
[0076] (1) Preparation of perovskite precursor solution: CsBr, PbBr2 and P123 reagents were mixed in a mass ratio of 83.3:8.3:0.3 and dissolved in DMSO to obtain a perovskite precursor solution.
[0077] (2) Preparation of perovskite light-emitting layer: Figure 1 The stacking order of the device structure shown is that the ITO substrate coated with the hole transport layer is transferred into the glove box and spin-coated with the perovskite precursor solution. The spin coating amount is 75 μL, the spin coating speed is 2000 rpm / min, and the spin coating time is 60 s. Then, heat treatment is performed at a temperature of 60°C for 1.5 min. The thickness of the perovskite light-emitting layer is 20 nm.
[0078] 4. Preparation of the Interface Layer
[0079] (1) Preparation of interface layer solution: PEI was dissolved in isopropanol to prepare a PEI organic solution with a concentration of 0.05 mg / mL.
[0080] (2) Preparation of interface layer: After preparing the perovskite light-emitting layer, the interface layer was treated in the glove box. The spin coating amount was 75 μL of PEI organic solution, the spin coating speed was 4000 rpm / min, and the spin coating time was 60 s. Then, the existing device (i.e., anode / hole transport layer / perovskite light-emitting layer / interface layer) was placed in a small transition chamber of the glove box, vacuumed for 10 minutes, and allowed to stand for 1 hour for vacuum drying.
[0081] 5. Preparation of Electron Transport Layer
[0082] (1) Preparation of electron transport layer solution: The electron transport material TPBi was dissolved in DMSO to prepare a TPBi solution with a concentration of 5 mg / mL.
[0083] (2) Preparation of electron transport layer: After the interface layer is prepared, the device is transferred from the small transition chamber to the glove box to prepare the electron transport layer. The spin coating amount is 75 μL, the spin coating speed is 2000 rpm / min, and the spin coating time is 60 s.
[0084] 6. Preparation of electron injection layer and cathode
[0085] After the electron transport layer is prepared, the device is transferred into a vacuum evaporation chamber for evaporation of the electron injection layer (LiF) and the cathode (Ag), wherein the thickness of the evaporated electron injection layer is 1 nm, and the thickness of the evaporated cathode is 100 nm.
[0086] 7. Electrical performance characterization
[0087] After the silver electrode cathode evaporation is completed, the device is placed in a glove box for characterization of electrical properties, namely the device's current, voltage, brightness, efficiency and other electrical properties.
[0088] Example 4
[0089] This embodiment provides a method for preparing a perovskite light emitting diode.
[0090] The structure of the perovskite light-emitting diode device provided in this embodiment is as follows Figure 1 As shown, anode (ITO) / hole transport layer (PEDOT:PSS:deionized water) / perovskite light-emitting layer / interface layer (PEI) / electron transport layer (TPBi) / / electron injection layer (LiF) / cathode (Ag).
[0091] 1. Cleaning of anode ITO substrate
[0092] The ITO substrate was ultrasonically cleaned in deionized water, anhydrous ethanol, acetone and isopropanol in sequence, with each ultrasonic cleaning lasting 20 minutes. After the ultrasonic cleaning, the ITO substrate was dried in an oven for more than 2 hours to ensure that the ITO substrate was completely dry and ready for use.
[0093] 2. Preparation of hole transport layer
[0094] (1) Preparation of hole transport layer solution: Take out the PEDOT:PSS aqueous solution from a 4°C refrigerator, leave it for half an hour until the solution returns to room temperature, mix deionized water and the PEDOT:PSS aqueous solution in a volume ratio of 1:1 to obtain a hole transport layer solution.
[0095] (2) Preparation of hole transport layer: The cleaned and dried ITO substrate was treated with ultraviolet light for 5 minutes to increase the surface affinity for liquid and facilitate the uniform distribution of the hole transport layer solution on the ITO substrate. The hole transport layer solution was filtered through a 0.22 μm aqueous filter head and then dripped onto the ITO substrate. The spin coating process was used at a speed of 3000 rpm / min for 60 seconds, followed by annealing at 130°C in air for 20 minutes. The thickness of the hole transport layer was 10 nm.
[0096] 3. Preparation of perovskite light-emitting layer
[0097] (1) Preparation of perovskite precursor solution: CsBr, PbBr2 and P123 reagents were mixed in a mass ratio of 83.3:8.3:0.3 and dissolved in DMSO to obtain a perovskite precursor solution.
[0098] (2) Preparation of perovskite light-emitting layer: Figure 1The stacking order of the device structure shown is that the ITO substrate coated with the hole transport layer is transferred into the glove box and spin-coated with the perovskite precursor solution. The spin coating amount is 75 μL, the spin coating speed is 2000 rpm / min, and the spin coating time is 60 s. Then, heat treatment is performed at a temperature of 60°C for 1.5 min. The thickness of the perovskite light-emitting layer is 20 nm.
[0099] 4. Preparation of the Interface Layer
[0100] (1) Preparation of interface layer solution: PEI was dissolved in isopropanol to prepare a PEI organic solution with a concentration of 0.20 mg / mL.
[0101] (2) Preparation of interface layer: After preparing the perovskite light-emitting layer, the interface layer was treated in the glove box. The spin coating amount was 75 μL of PEI organic solution, the spin coating speed was 4000 rpm / min, and the spin coating time was 60 s. Then, the existing device (i.e., anode / hole transport layer / perovskite light-emitting layer / interface layer) was placed in a small transition chamber of the glove box, vacuumed for 10 minutes, and allowed to stand for 1 hour for vacuum drying.
[0102] 5. Preparation of Electron Transport Layer
[0103] (1) Preparation of electron transport layer solution: The electron transport material TPBi was dissolved in DMSO to prepare a TPBi solution with a concentration of 5 mg / mL.
[0104] (2) Preparation of electron transport layer: After the interface layer is prepared, the device is transferred from the small transition chamber to the glove box to prepare the electron transport layer. The spin coating amount is 75 μL, the spin coating speed is 2000 rpm / min, and the spin coating time is 60 s.
[0105] 6. Preparation of electron injection layer and cathode
[0106] After the electron transport layer is prepared, the device is transferred into a vacuum evaporation chamber for evaporation of the electron injection layer (LiF) and the cathode (Ag), wherein the thickness of the evaporated electron injection layer is 1 nm, and the thickness of the evaporated cathode is 100 nm.
[0107] 7. Electrical performance characterization
[0108] After the silver electrode cathode evaporation is completed, the device is placed in a glove box for characterization of electrical properties, namely the device's current, voltage, brightness, efficiency and other electrical properties.
[0109] Example 5
[0110] This embodiment provides a method for preparing a perovskite light emitting diode.
[0111] The structure of the perovskite light-emitting diode device provided in this embodiment is as follows Figure 1 As shown, anode (ITO) / hole transport layer (PEDOT:PSS:deionized water) / perovskite light-emitting layer / interface layer (PEI) / electron transport layer (TPBi) / / electron injection layer (LiF) / cathode (Ag).
[0112] 1. Cleaning of anode ITO substrate
[0113] The ITO substrate was ultrasonically cleaned in deionized water, anhydrous ethanol, acetone and isopropanol in turn, and the ultrasonic time was 20 minutes each time. After the ultrasonic treatment, the ITO substrate was dried in an oven for more than 2 hours to ensure that the ITO substrate was completely dry and ready for use. The cleaned and dried ITO substrate was treated with ultraviolet light for 5 minutes to facilitate the uniform distribution of the hole transport layer solution on the ITO substrate.
[0114] 2. Preparation of hole transport layer
[0115] (1) Preparation of hole transport layer solution: Take out the PEDOT:PSS aqueous solution from a 4°C refrigerator, leave it for half an hour until the solution returns to room temperature, mix deionized water and the PEDOT:PSS aqueous solution in a volume ratio of 1:1 to obtain a hole transport layer solution.
[0116] (2) Preparation of hole transport layer: The hole transport layer solution was filtered through a 0.22 μm aqueous filter head and then dropped onto the ITO substrate. The solution was spin-coated at a speed of 3000 rpm / min for 60 s and then annealed in air at 130° C. for 20 min. The thickness of the hole transport layer was 10 nm.
[0117] 3. Preparation of perovskite light-emitting layer
[0118] (1) Preparation of perovskite precursor solution: CsBr, PbBr2 and P123 reagents were mixed in a mass ratio of 83.3:8.3:0.3 and dissolved in DMSO to obtain a perovskite precursor solution.
[0119] (2) Preparation of perovskite light-emitting layer: Figure 1 The stacking order of the device structure shown is that the ITO substrate coated with the hole transport layer is transferred into the glove box and spin-coated with the perovskite precursor solution. The spin coating amount is 75 μL, the spin coating speed is 2000 rpm / min, and the spin coating time is 60 s. Then, heat treatment is performed at a temperature of 60°C for 1.5 min. The thickness of the perovskite light-emitting layer is 20 nm.
[0120] 4. Preparation of the Interface Layer
[0121] (1) Preparation of interface layer solution: PEI was dissolved in isopropanol to prepare a PEI organic solution with a concentration of 1.00 mg / mL.
[0122] (2) Preparation of interface layer: After preparing the perovskite light-emitting layer, the interface layer was treated in the glove box. The spin coating amount was 75 μL of PEI organic solution, the spin coating speed was 4000 rpm / min, and the spin coating time was 60 s. Then, the existing device (i.e., anode / hole transport layer / perovskite light-emitting layer / interface layer) was placed in a small transition chamber of the glove box, vacuumed for 10 minutes, and allowed to stand for 1 hour for vacuum drying.
[0123] 5. Preparation of Electron Transport Layer
[0124] (1) Preparation of electron transport layer solution: The electron transport material TPBi was dissolved in DMSO to prepare a TPBi solution with a concentration of 5 mg / mL.
[0125] (2) Preparation of electron transport layer: After the interface layer is prepared, the device is transferred from the small transition chamber to the glove box to prepare the electron transport layer. The spin coating amount is 75 μL, the spin coating speed is 2000 rpm / min, and the spin coating time is 60 s.
[0126] 6. Preparation of electron injection layer and cathode
[0127] After the electron transport layer is prepared, the device is transferred into a vacuum evaporation chamber for evaporation of the electron injection layer (LiF) and the cathode (Ag), wherein the thickness of the evaporated electron injection layer is 1 nm, and the thickness of the evaporated cathode is 100 nm.
[0128] 7. Electrical performance characterization
[0129] After the silver electrode cathode evaporation is completed, the device is placed in a glove box for characterization of electrical properties, namely the device's current, voltage, brightness, efficiency and other electrical properties.
[0130] Example 6
[0131] This example provides the electrical properties of perovskite light-emitting diodes prepared from PEI organic solutions with different concentrations.
[0132] The present invention tests the electrical properties of the perovskite light-emitting diodes prepared in Examples 2 to 5, such as current density, voltage, and brightness, to obtain a JV curve and a LV curve.
[0133] JV curve Figure 3 As shown in the figure, with the increase of the concentration of PEI organic solution in the interface layer solution, the current density shows a downward trend. This is because the existence of the interface layer affects the transport of carriers, causing the electrical properties of the diode device to change.
[0134] LV curve Figure 4As shown in the figure, with the increase of the concentration of PEI organic solution in the interface layer, the brightness of the device first increases and then decreases. In this process, the concentration of the interface layer solution first changes the thickness and density of PEI in the interface layer. When the concentration of PEI organic solution is low, the interface layer plays a good role in suppressing interface loss and improving energy relations, promoting the effective recombination of carriers, and significantly improving the brightness of the device; when the concentration of PEI organic solution gradually increases, the excessive thickness and density of the interface layer hinder the transmission of carriers, resulting in a significant decrease in performance.
[0135] The embodiments described above are part of the embodiments of the present invention, but not all of them. The detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but only represents selected embodiments of the present invention. All other embodiments obtained without creative work and related deductions and substitutions made by ordinary technicians in the field under the conditions of the concept of the present invention belong to the scope of protection of the present invention.
Claims
1. A perovskite light-emitting diode, comprising a hole transport layer, a perovskite light-emitting layer, an electron transport layer, an electron injection layer and a cathode sequentially arranged on an anode substrate, characterized in that: It also includes an interface layer made by spin coating of a PEI organic solution, and the interface layer is arranged between the perovskite light-emitting layer and the electron transport layer.
2. A method for preparing the perovskite light-emitting diode according to claim 1, characterized in that: include: A hole transport layer, a perovskite light-emitting layer, the interface layer, and an electron transport layer are sequentially spin-coated on an anode substrate using a solution method; Then, an electron injection layer and a cathode are sequentially vacuum-deposited on the electron transport layer.
3. The method according to claim 2, characterized in that The anode substrate is sequentially subjected to continuous ultrasonic cleaning with deionized water, anhydrous ethanol, acetone and isopropanol for at least 20 to 30 minutes each; Then, the anode substrate is subjected to surface treatment; The surface treatment is any one of plasma bombardment surface treatment and ultraviolet light treatment.
4. The method according to claim 2, characterized in that: The hole transport layer is prepared by spin coating PEDOT:PSS and then annealing; The PEDOT:PSS is a PEDOT:PSS solution and water ultrasonically mixed in a volume ratio of 1:1 for 2 hours; The spin coating speed is 2000-4000 rpm / min, and the spin coating time is 50-60 s; The annealing temperature is 130-150° C., the annealing time is 15-20 min, and the annealing environment is air.
5. The method according to claim 2, characterized in that: The perovskite light-emitting layer is prepared by spin coating a perovskite precursor solution and then heat treating it; The perovskite precursor solution is prepared by dissolving CsBr, PbBr2 and P123 in N,N-dimethylformamide DMF or DMSO; The spin coating rotation speed is 2000-4000 rpm / min, the spin coating time is 50-60 s, and the spin coating environment is nitrogen; The heat treatment temperature is 50-80° C., the heat treatment time is 1-3 min, and the heat treatment environment is nitrogen.
6. The method according to claim 5, characterized in that The mass ratio of CsBr, PbBr2 and P123 is 8.33:8.3:0.
3.
7. The method according to claim 2, characterized in that: The interface layer is prepared by spin coating of PEI organic solution; The PEI organic solution is PEI dissolved in isopropanol, and the concentration of the PEI organic solution is 0.05-1 mg / mL; The spin coating has a rotation speed of 2000 to 5000 rpm / min, and the spin coating time is 50 to 65 s.
8. The method according to claim 2, characterized in that: The electron transport layer is prepared by spin coating of TPBi solution; The TPBi solution is TPBi dissolved in DMF or DMSO, and the concentration of the TPBi solution is 3-5 mg / mL; The rotation speed of the spin coating is 1000-3000 rpm / min, and the spin coating time is 50-65 s.
9. The method according to claim 2, characterized in that: The electron injection layer is LiF, and the thickness of the electron injection layer is 0.3-1 nm; The cathode is any one of metal silver and aluminum, and the thickness of the cathode is 80-150 nm.
10. The method according to claim 2, characterized in that The steps include: S1. Surface treatment of the anode substrate after cleaning and drying; S2. Spin-coating PEDOT:PSS on the surface of the anode substrate described in S1 and annealing to obtain a hole transport layer; S3. Spin-coating a perovskite precursor solution on the hole transport layer described in S2, and obtaining a perovskite light-emitting layer after heat treatment; S4. After spin coating the PEI organic solution on the perovskite light-emitting layer described in S3, vacuum drying is performed to obtain an interface layer; S5. Spin coating the TPBi solution on the interface layer described in S4 to obtain an electron transport layer; S6. Vacuum evaporate an electron injection layer and a cathode on the electron transport layer described in S5.